Participatory Action Research with a Group of Urban First Nations Grandmothers: Decreasing Inequities through Health Promotion - Ginn, Carla S; Kulig, Judith C (International Indigenous Policy Journal, 2015)
Inequities experienced by Aboriginal people in Canada due to residual effects of colonization and assimilation are evident; research is needed focusing on positive strategies for health and healing in urban settings. Participatory action research (PAR) is identified as an appropriate method of research for engaging collaboratively with Aboriginal people. This study involved seven First Nations grandmothers in a small urban community in Alberta, Canada. The grandmothers linked personal health with family and community health, and practiced health promotion through maintaining cycles of support between themselves, their families, and communities. These grandmothers recognized their invaluable roles as leaders in health promotion in families and communities. The collective knowledge of Aboriginal grandmothers has potential to affect health inequities on a broader scale.